DETERMINASI KINERJA PEGAWAI DISPENDUKCAPIL KOTA KEDIRI DITINJAU DARI BEBAN KERJA, PENGAWASAN KERJA, DAN LINGKUNGAN KERJA - Setiawati , Rini Eka; Leksono, Poniran Yudho (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
Knowing and analyzing the effect of workload, work supervision and work environment on employee performance at the Department of Population and Civil Registration of Kediri City partially & simultaneously is the goal to be achieved in this study. Quantitative approach to this research, the technique uses causality. All employees of the Department of Population and Civil Registration of Kediri City totaling 40 people are the population and the sample, multiple linear regression is the method of calculation. The result is that there is influence of workload, work supervision, and work environment on employee performance at the Department of Population and Civil Registration of Kediri City.